Kenya: Recent developments in public agricultural research - Flaherty, Kathleen; Murithi, Festus M.; Mulinge, Wellington; Njuguna, Esther (International Food Policy Research Institute, 2010)
Since the early 1990s, public agricultural research and development (R&D) spending in Kenya has varied considerably from year to year, while agricultural research capacity showed a more stable trend.1 In 2008, Kenya spent 4.5 billion Kenyan shillings or 154 million PPP dollars (both in 2005 constant prices) on agricultural R&D. Unless otherwise stated, all investment data in this note are expressed in purchasing power parity (PPP) prices. PPPs reflect the purchasing power of currencies more effectively than do standard exchange rates because they compare the prices of a broader range of local-as opposed to internationally traded-goods and services. Agricultural R&D spending increased modestly during the 1980s, when several government and higher education agencies involved in agricultural research were established. The variation in spending since the early 1990s, however, was mostly the effect of fluctuations in donor funding and, to a lesser extent, government contributions to KARI.